An Alternative Pathway for Formononetin Biosynthesis in Pueraria lobata - Li, Jia; Li, Changfu; Gou, Junbo; Wang, Xin; Fan, Rongyan; Zhang, Yansheng (Frontiers in Plant Science, 2016)
The O-methylation is an important tailing process in Pueraria lobata isoflavone metabolism, but the molecular mechanism governing it remains not elucidated. This manuscript describes the mining of key O-methyltransferases (OMTs) involved in the process. Using our previously constructed P. lobata transcriptome, the OMT candidates were searched, extensively analyzed and their functions were investigated by expression in yeast, Escherichia coli or Glycine max hairy roots. Here we report the identification of the key OMT gene responsible for formononetin production in P. lobata (designated as PlOMT9). PlOMT9 primarily functions as an isoflavone specific 4′-O-methyltransferase, although it shows high sequence identities with isoflavone 7-O-methyltransferases. Moreover, unlike the previously reported OMTs that catalyze the 4′-O-methylation for formononetin biosynthesis at the isoflavanone stage, PlOMT9 performs this modifying step at the isoflavone level, using daidzein rather than 2,7,4′-trihydroxy-isoflavanone as the substrate. Gene expression analyses and metabolite profiling supported its proposed roles in P. lobata. Using the system of transgenic Glycine max hairy roots, the role of PlOMT9 in the biosynthesis of formononetin was further demonstrated in vivo.